Gastrointestinal Symptoms Related to Potato Ingestion During Cycling in Trained Athletes (P23-012-19). (13th June 2019) - Scaroni, Susannah; Salvador, Amadeo; McKenna, Colleen; Alamilla, Rafael; Martinez, Isabel; Cloud, Ryan M; Miltko, Adriana; Keeble, Alex; Paluska, Scott; Broad, Elizabeth; Burd, Nicholas
Abstract: Objectives: Carbohydrate (CHO) ingestion is an established nutritional strategy to improve endurance performance, yet currently available products may contribute to gastrointestinal (GI) distress. Potatoes have a high-glycemic index, indicating that their CHO content is readily available. We aimed to compare the effects of ingesting potato purée (POT), commercial CHO gel (GEL), or a control (water, CTL) during cycling on GI Symptoms and affective indices in trained athletes. Methods: In a randomized crossover study, twelve trained cyclists (9 M and 3F; 30.5 ± 8.7y; 70.6 ± 7.6 kg; 1.70 ± 7 cm; 60.7 ± 8.9 mL/kg/min) completed a 2 h cycling challenge (60–85%VO2 max) followed by a 6 kJ/kg time trial. Cyclists were randomly assigned to consume POT, GEL, or CTL during the challenge. Rating of perceived exertion (RPE), GI symptoms, and affective responses (Feeling Scale −5/+5) were collected throughout the challenge via visual analog scales. Differences between treatments were assessed by mixed model analysis of variance using time and condition as a fixed factor and subject as a random factor. All data represent mean ± standard deviation. Results: RPE was not different between POT, GEL, or CTL condition at the end of the cycling challenge (POT: 17 ± 1; GEL: 17 ± 1, CTL: 18 ± 1, P > 0.05). Higher GI symptoms ( P < 0.01) were observed at the end of the challenge during POT condition (15 ± 3%) when compared to GEL (8 ± 3%) and CTL (7 ± 3%), with no significant difference in these symptoms prior to this time. FS response significantly increased ( P = 0.04) during POT trial (2 ± 2) compared to GEL (0 ± 0.2) and CTL (0 ± 2) conditions at end of the challenge. Conclusions: While POT ingestion resulted in greater GI distressed compared to CHO gel, cyclists perceived the exertion to be similar and even reported feeling more pleasant after POT ingestion in endurance exercise. Funding Sources: Alliance for Potato Research and Education.